Makna Kehidupan Rohani dalam Panggilan Orang yang Percaya Menurut 1 Petrus 1:13-16 - Jeni Murni Gulo; Selvi Ina Kii; Malik Bambangan (Jurnal Teologi Injili dan Pendidikan Agama, 2025)
In the calling of believers, the meaning of spiritual life refers to a strong relationship between a person and their faith, which influences their actions, values, and life goals. Spiritual life is not just about personal piety; it is also an essential part of a believer’s mission, ministry, and relationship with God. It is a journey of transformation that encourages believers to align their lives with divine will and to actively participate in the wider community of faith. This calling encourages believers to pursue their purpose, encouraging moral progress, spiritual maturity, and a sense of responsibility toward others. By living a spiritual life, a person can gain a better understanding of the believer’s place in this world and how they can live according to God’s design.